Análise dos aspectos facilitadores e barreiras para o compartilhamento do conhecimento: estudo de caso em empresa de consultoria de informática médio porte - Alves, Márcia (2010)
This paper aims to analyze aspects that may have an influence - favorably or unfavorably - on the sharing of knowledge in the organization. Therefore, it is important to understand the foundation of willingness to share knowledge, which is based on the individual's behavior, affected not only by his features and personal values, but also shaped by the values of the group and organization where he operates (ANGELONI, 2002). A bibliographical research on the subject was conducted through articles, theses, books and a field survey. It included the following subjects: Knowledge Management, Knowledge in the Organization, organizational Culture, and Behavioral Factors that affect Knowledge Sharing and its Barriers and Facilitators. A questionnaire was developed based on the literature, and applied to employees of the company's case study. Through this questionnaire it was possible to detect the barriers and facilities found in sharing knowledge on the project's environment. The results showed that sharing knowledge is part of the culture of the company "X" despite the collaborators poor visibility of the organization's intention to invest in the subject-matter. Finally, an action plan was proposed to suit the best practices of knowledge management in the organization, prioritizing actions in the short, medium and long term, related to strategic and operational objectives